2010
DOI: 10.3141/2180-14
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Susceptibility of High and Low Compaction Dry Process Crumb Rubber–Modified Asphalt Mixtures

Abstract: The field performance of dry process Crumb Rubber Modified (CRM) asphalt mixtures has been reported to be inconsistent with stripping and premature cracking on the surfacing. One of the concerns is that, as achieving field compaction of CRM material is difficult because of the inherent resilient nature of the rubber particle, non-uniform field compaction may lead to deficient bond between rubber and bitumen. To assess the influence of compaction, a series of CRM and control mixtures were produced and were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In the dry process, most of the previous works have considered that the wet process had sufficient interaction between asphalt and CRM due to long time blending at high temperature, while asphalt -CRM reaction in the dry process is negligible due to the shorter reaction period and larger particle sizes used (Rahman 2004). However, recent research found that during the mixing period as well as transportation and laying, the asphalt -CRM reaction in the dry process is significantly higher than previously thought and improves the performance of HMA (Singleton 2000, Rahman et al 2010, Hernández-Olivares et al 2009, López-Moro et al 2013. In addition, field performance of the dry process CRM mixture is inconsistent and the service life varies from 2 to 20 years (Rahman 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the dry process, most of the previous works have considered that the wet process had sufficient interaction between asphalt and CRM due to long time blending at high temperature, while asphalt -CRM reaction in the dry process is negligible due to the shorter reaction period and larger particle sizes used (Rahman 2004). However, recent research found that during the mixing period as well as transportation and laying, the asphalt -CRM reaction in the dry process is significantly higher than previously thought and improves the performance of HMA (Singleton 2000, Rahman et al 2010, Hernández-Olivares et al 2009, López-Moro et al 2013. In addition, field performance of the dry process CRM mixture is inconsistent and the service life varies from 2 to 20 years (Rahman 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research found that during the mixing period as well as transportation and laying, the asphalt -CRM reaction in the dry process is significantly higher than previously thought and improves the performance of HMA (Singleton 2000, Rahman et al 2010, Hernández-Olivares et al 2009, López-Moro et al 2013). In addition, field performance of the dry process CRM mixture is inconsistent and the service life varies from 2 to 20 years (Rahman 2004).…”
Section: Introductionmentioning
confidence: 87%
“…Crumb rubber-asphalt mixture is a new type of deicing pavement material prepared by replacing some of the aggregates in asphalt mixture with mechanically sheared particles of waste rubber tires and mixing them uniformly with high-performance modified asphalt [1][2][3][4][5][6]. The addition of rubber crumbs changes the original structure of the mixture and the contact state between the materials so that the pavement is more easily loosened than an ordinary asphalt pavement [7].…”
Section: Introductionmentioning
confidence: 99%